Treatment of Influenza Infection of Mice by Using Rimantadine Hydrochlorides by the Aerosol and Intraperitoneal Routes - Stephen, Edward L. (1975)
Rimantadine hydrochloride was administered for 4 days in a small-particle (95% < 6.5 μm) aerosol (8.8 mg/kg per day) or intraperitoneally (40 mg/kg per day) to mice previously infected with influenza A/Aichi/2/68 (H(3)N(2)), mouse adapted. Mean time to death and incidence of survival were significantly increased in all treated groups of mice. The rate of eventual disappearance of virus from lung tissue was also accelerated by therapy. However, maximal mean virus titer per lung, and lung histopathology, did not reveal any difference between control and either group of treated mice. Aerosol therapy initiated at 72 h postinfection was as effective as that initiated at 6 h, even though lung virus titers of these mice had already peaked by 72 h. In contrast, intraperitoneal therapy initiated at 72 h was not effective in all studies.